Effect of Cricket (Acheta domesticus) Flour Added to Mixture Powder to Obtain a Traditional Beverage (Chucula) on Its Physicochemical Characteristics - Ariadna Montoro; Luz Indira Sotelo-Díaz; Annamaria Filomena-Ambrosio; Marta Igual; Javier Martínez-Monzó; Purificación García-Segovia (Biology and Life Sciences Forum, 2021)
The aim of this study was to add cricket (Acheta domesticus) flour to dried mixtures of chucula to obtain a mixture with higher protein content without altering the typical properties of the traditional product. An experimental design with three factors (cricket flour, cacao and other flours) was performed. From this, 27 experiments were carried out. The water and protein content, particle size, water solubility and water absorption index, and color of samples were determined. All samples presented water content values less than or equal to 3%, typical of this type of product. Crude protein content increased significantly with increasing cricket flour content. The particle size of the samples with lower cocoa contents were higher, however those with lower cricket flour contents were lower. The water absorption and solubility indices were not affected by the factors in the ranges studied. The sample with lower content of the generic flours presented lower luminosity values, that is, they were darker. The sample with the highest cocoa content in its formulation showed more orange-reddish tones compared to the rest. The addition of cricket flour could be an alternative to increase the protein content in powdered chucula without altering its traditional characteristics. According to results, 7% of cricket flour, 25% of cacao and 68% of general flour was recommended to improve the final product.